The Role of Leadership in the Knowledge Management and Innovation Processes in a Modern Organization - Atkočiūnienė, Zenona Ona; Siudikienė, Daiva; Girnienė, Ingrida (Information & Media, 2019)
The ability to create innovations is one of the most important sources of a competitive advantage forevery modern organization, region, and state. In today’s context as a particularly significant problem arises the issue of the role of leaders in organizing effective knowledge management and innovation processes. Although the topic of leadership was analyzed quite extensively in the second half of the 20th century, in the 21st century, it is recognized that organizations of this age need a new quality of leadership, as the organizations themselves and their environments are undergoing profound changes. This paper analyzes the changing approaches to leadership and its role in a modern organization, focusing on the concept of innovative leadership and its peculiarities in order to identify the components of this phenomenon and their links to knowledge management and innovation processes. After analyzing significant aspects of this topic, identified were the relationships between innovative leadership, knowledge management, and innovation performance, as well as an integral theoretical model of innovative leadership, knowledge management, and innovation performance for driving continuous innovation performance has been developed.
Keywords: innovative leadership; leadership expression; leader communication; information and knowledge management; innovation